Assessment of Myocardial Ischemia in Obese Individuals Undergoing Physical Stress Echocardiography (PSE) - Silveira,Mara Graziele Maciel (2015)
Background: Physical stress echocardiography is an established methodology for diagnosis and risk stratification of coronary artery disease in patients with physical capacity. In obese (body mass index ≥ 30 kg/m2) the usefulness of pharmacological stress echocardiography has been demonstrated; however, has not been reported the use of physical stress echocardiography in this growing population group. Objective: To assess the frequency of myocardial ischemia in obese and non-obese patients undergoing physical stress echocardiography and compare their clinical and echocardiographic differences. Methods: 4,050 patients who underwent treadmill physical stress echocardiography were studied according to the Bruce protocol, divided into two groups: obese (n = 945; 23.3%) and non-obese (n = 3,105; 76.6%). Results: There was no difference regarding gender. Obese patients were younger (55.4 ± 10.9 vs. 57.56 ± 11.67) and had a higher frequency of hypertension (75.2% vs. 57, 2%; p < 0.0001), diabetis mellitus (15.2% vs. 10.9%; p < 0.0001), dyslipidemia (59.5% vs 51.9%; p < 0.0001), family history of coronary artery disease (59.3% vs. 55.1%; p = 0.023) and physical inactivity (71.4% vs. 52.9%, p < 0.0001). The obese had greater aortic dimensions (3.27 vs. 3.14 cm; p < 0.0001), left atrium (3.97 vs. 3.72 cm; p < 0.0001) and the relative thickness of the ventricule (33.7 vs. 32.8 cm; p < 0.0001). Regarding the presence of myocardial ischemia, there was no difference between groups (19% vs. 17.9%; p = 0.41). In adjusted logistic regression, the presence of myocardial ischemia remained independently associated with age, female gender, diabetes and hypertension. Conclusion: Obesity did not behave as a predictor of the presence of ischemia and the physical stress echocardiography. The application of this assessment tool in large scale sample demonstrates the feasibility of the methodology, also in obese.